Attitude of the Rural Elite Farmers towards Extension Activities Performed by Personnel of Department of Agricultural Extension - Arifullah, M; Zahan, A; Rana, MM; Adil, M; Shamsunnaher, Shamsunnaher (The Agriculturists, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The main purpose of the study was to ascertain the attitude of rural elite farmers towards extension activities performed by Upazilla Agricultural Extension personnel of DAE and to explore the relationship between the selected characteristics of the respondents and their extent of attitude towards those extension activities under reference. The study was conducted in two unions, namely Ratanpur and Rasullabad covering 5 villages of Nabinagar Upazilla under Brahmanbaria District. Data were collected from the rural elite farmers using a pre- tested interview schedule during 15th May 2009 to 10th June 2009. It was found that the highest proportion (43.14%) of the respondents had moderate favourable attitude compared to 33.33 percent having high favourable attitude and 23.53 percent less favourable attitude. Pearson Product Moment Correlation (r) test was used to ascertain the relationships between the concerned dependent and independent variables of the study. Findings revealed that education, farm size, time spent for farm work, organizational participation, extension contact and knowledge on agriculture of elite rural farmers showed positive significant relationship while age and annual family income did not show any such relationship with their attitude towards extension activities performed by Upazilla Agricultural Extension Personnel of DAE. DOI: http://dx.doi.org/10.3329/agric.v12i1.19586 <span style="font-size: 12.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The Agriculturists <span style="font-size: 11.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">2014<span style="font-size: 12.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">; 1<span style="font-size: 11.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">2(1) 96-102<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>